The Effect Of Organizational Agility On Organizational Performance In Class I Correctional Institutions In Palembang - Muhammad Salim Jindan; Kusmiyanti Kusmiyanti (UNIVED Press, 2025)
The President of the Republic of Indonesia, Prabowo Subianto, issued Law No. 1 Year 2025 on Expenditure Efficiency in the Implementation of the APBN / D at Ministries / Institutions. The IMIPAS Ministry as a new institution is required to be able to adapt to dynamic efficiency and restructuring policies. Organizational agility theoretically plays an important role in maintaining organizational performance, especially in the Prison Technical Implementation Unit. This study aims to determine the effect of organizational agility on organizational performance at Class I Palembang Correctional Institution. The research method used is quantitative with probability sampling technique based on the Krejcie and Morgan formula, so that 91 respondents were obtained. Data collection was done through a Google Form questionnaire with 22 statement indicators. Data analysis includes validity, reliability, normality, simple linear regression, significance, and determination tests using SPSS version 25. The test results show a significance value of 0.000 <0.05, so H0 is rejected and Ha is accepted. R square of 0.753 shows that organizational agility affects organizational performance by 75.3%, while 24.7% is influenced by other factors. In conclusion, there is a positive and significant influence between organizational agility on organizational performance at Class I Palembang Correctional Instititution.